Voting Rules and Budget Allocation in an Enlarged EU - Heikki Kauppi; Mika Widgrén (Aboa Centre for Economics (ACE), 2006)
EU declares to provide support for the rural and poor regions of its member states. However, recent research shows that past EU budget allocations (in EU-15) can be attributed to measures of the distribution of voting power in the Council of Ministers deciding on the bulk of EU spending. A standard power measure alone can explain about 85% of the variance of the past EU budget shares, while, if stable coalition patterns among member countries are taken into account, power can explain at least 95% of the budget allocation. In this paper we use such estimates to predict EU budget shares after the eastern enlargement. According to our estimates eastern enlargement has large effects on the budget receipts of the incumbent member states. Moreover, whether the voting rules are based on the Nice Treaty (NT) or the Constitutional Treaty (CT) makes a difference for most member states. Many member states would be worse off under CT than under NT.
Keywords: C71; D70; D72; 330; EU budget; voting power; Constitutional Treaty; Treaty of Nice